Pulsed FCAW of Martensitic Stainless Clads onto Mild Steel: Microstructure, Hardness, and Residual Stresses - Moreno, Joao Sartori; Conde, Fabio Faria; Correa, Celso Alves; Barbosa, Luiz Henrique; Silva, Erenilton Pereira da; Avila, Julian [UNESP]; Buzolin, Ricardo Henrique; Pinto, Haroldo Cavalcanti (MDPI, 2022)
The low carbon martensitic stainless AWS 410NiMo steel has in its chemical composition 13% chromium, 4% nickel, and 0.4% molybdenum (wt.%) and is used in turbine recovery, rotors, and high-pressure steam pump housings due to its resistance to impact at low temperatures, as well as to corrosion and cavitation. Those applications of the AWS 410NiMo steel frequently demand repair, which is performed by welding or cladding. Arc welding is a well-established technique for joining materials and presents several parameters that influence the mechanical performance of the weld bead. Although numerous welding processes exist, optimizing welding parameters for specific applications and materials is always challenging. The present work deals with a systematic study to verify the correlation between the pulsed fluxed core arc welding (FCAW) parameters, namely pulse current and frequency, welding speed, and contact tip work distance (CTWD), and the bead morphology, microstructure formation, residual stress, and hardness of the martensitic clad. The substrate used was the AISI 1020 steel, and the AWS 410NiMo steel was the filler metal for clad deposition. From the initial nine (9) samples, three (3) were selected for in-depth characterization. Lower heat input resulted in lower dilution, more elevated hardness, and lower compressive residual stresses. Therefore, the results highlight the need for selecting the proper heat input, even when using a pulsed FCAW procedure, to achieve the desired performance of the clad. In the present case, a higher heat input appears to be more advantageous owing to the lower convexity index, smooth hardness transition between fusion and heat-affected zones in addition to more elevated compressive stresses.
Keywords: cladding; FCAW; interfacewhere(Figurea package10h)morphologyhad an amountof clustersof martensitewas alsoformationformed; lowbainiticmagnificationone. The weldviewlineof FZ; martensitic stainless steel; mechanical properties; residual stresses